1999
DOI: 10.1037/h0080379
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum affect and depressive symptoms in mothers and fathers.

Abstract: In a study of the postpartum affective experiences of couples, mothers and fathers completed questionnaires on coping, marital satisfaction, stress, positive and negative affect, and depression one month pre- and then one month postpartum. More than one-fourth of both mothers and fathers reported elevated depressive symptoms, which correlated significantly between parents. Prepartum coping, stress, and affect significantly predicted postpartum affect. Research and clinical applications of the findings are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 44 publications
(54 reference statements)
4
77
1
5
Order By: Relevance
“…Lung et al (2009aLung et al ( , 2009b found that the mental health states of the father and mother were positively correlated with each other, and that when mothers had better mental health, fathers did too, and vice versa. This is consistent with previous studies which found that depression in one partner is correlated with depression in the other (Ballard et al, 1994;Ramchandani et al, 2008;Soliday et al, 1999). In further investigation, we found that the mental health of parents with children at high risk of autism spectrum disorder was not affected by the children's developmental condition, but rather, by maternal mental health.…”
Section: Reciprocal Association Between Parental Mental Health and Chsupporting
confidence: 80%
“…Lung et al (2009aLung et al ( , 2009b found that the mental health states of the father and mother were positively correlated with each other, and that when mothers had better mental health, fathers did too, and vice versa. This is consistent with previous studies which found that depression in one partner is correlated with depression in the other (Ballard et al, 1994;Ramchandani et al, 2008;Soliday et al, 1999). In further investigation, we found that the mental health of parents with children at high risk of autism spectrum disorder was not affected by the children's developmental condition, but rather, by maternal mental health.…”
Section: Reciprocal Association Between Parental Mental Health and Chsupporting
confidence: 80%
“…Las investigaciones sugieren que la depresión en un miembro de la pareja se correlaciona considerablemente con la depresión en el otro. 6,7,3,8 Un estudio demostró que entre el 24 y el 50 por ciento de los hombres con PPD paterna también tenía pareja con PPD. 9 Esto indica que hay una alta probabilidad de que los bebés se puedan encontrar en situaciones familiares en donde varios de los cuidadores están deprimidos, lo que puede derivar en alteraciones más graves en el desarrollo del bebé.…”
Section: Prevalencia De La Depresión Posparto Paternaunclassified
“…Las investigaciones sugieren que la depresión en un miembro de la pareja se correlaciona considerablemente con la depresión en el otro. 6,7,3,8 Un estudio demostró que entre el 24 y el 50 por ciento de los hombres con PPD paterna también tenía pareja con PPD.…”
unclassified
“…The highest depression rates were noticed in the period between the third and sixth month postpartum (25.6%), and the lowest in the first three months of the child's life (7.7%). Soliday et al [15] stated that 25.5% of the total number of fathers with postnatal depression, 69% were diagnosed with mild depression, and 30.8% with moderate depression. When the length of the depression was considered, it was found that among the 10% of fathers who were diagnosed with depression six weeks postpartum, 54% suffered from depression at least for another six months [16].…”
Section: Research On Paternal Postnatal Depres-sion -A Reviewmentioning
confidence: 99%